Demyelination Disorders - Baloyannis, Stavros J.; Rossi, Fabian H.; Liu, Welwin (IntechOpen, 2022)
Demyelination disorders are among the most frequent neurological conditions. Types of these disorders include multiple sclerosis, Guillain Barré syndrome, diabetic peripheral neuropathy, entrapment neuropathies, and others, all of which can result in serious physical incapacity and diminished quality of life. This book examines various aspects of demyelination from clinical, diagnostic, and therapeutic points of view. Chapters address different types of demyelination diseases, their associated mechanisms, and pharmacologic and nonpharmacologic treatment approaches, among other topics.